2019
DOI: 10.4244/eij-d-19-00318
|View full text |Cite
|
Sign up to set email alerts
|

In vivo intravascular photoacoustic imaging of plaque lipid in coronary atherosclerosis

Abstract: Prospective identification of lipid-rich vulnerable plaque has remained an elusive goal. Intravascular photoacoustics, a hybrid optical and ultrasonic technology, was developed as a tool for lipid-rich plaque imaging. Here, we present the first in vivo images of lipid-rich coronary atherosclerosis acquired with this new technology in a large animal model, and relate them to independent catheter-based imaging and histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…A study in an atherosclerotic animal model is ongoing. 33 Can the assessment of local haemodynamic forces improve the identification of vulnerable plaques and patients?…”
Section: Imaging Of the High-risk/culprit Coronary Plaquementioning
confidence: 99%
“…A study in an atherosclerotic animal model is ongoing. 33 Can the assessment of local haemodynamic forces improve the identification of vulnerable plaques and patients?…”
Section: Imaging Of the High-risk/culprit Coronary Plaquementioning
confidence: 99%
“…In contrast to these transabdominal imaging approaches described above, several studies have also utilized catheter-based approaches ex vivo [ 47 , 53 , 54 ], in animal models [ 48 , 55 ] or human samples [ 49 , 50 ], with laser illumination around 930 nm for detecting the peak absorption of lipids in the first NIR window ( Figure 1 ). Other studies aimed to increase the specificity of OAI for identification of carotid atherosclerosis by targeted approaches.…”
Section: Optoacoustic Imaging Of Inflammation: Applicationsmentioning
confidence: 99%
“…Recently, Iskandder-Risk et al demonstrated IVPA in vivo imaging of swine coronary artery. The quality of images were adjudicated using OCT and histology ( 79 ).…”
Section: Photoacoustic Imagingmentioning
confidence: 99%